A Study on Anne Tyler’s Select Novels with Rhonda Byrne’s The Secret (International Journal of Food and Nutritional Sciences, 2022)
An American Pulitzer prizewinning novelist Anne Tyleris renowned for her thematic insights into ordinary lives with a tone of optimism. Her novels reveal the truth of women's stereotypical existence insisting that they could achieve anything if their mind is fixed upon it. In this regard, the Australian television writer, Rhonde Byrnes’s book of The Secret is compared and contrasted with the women characters of Anne Tyler.These women believe that, everything will change in life, if the inner mind prompts her to achieve certain things. Byrne’s concept of the law of attraction holds a strong note which " tells us whatever we will believe, we will manifest" (S26). Simultaneously, the women protagonists of Tyler propel towards creating new spaces for themselves where they are not constrained to do the household chores restricting themselves.